Mitochondria, Oxidative Stress, cAMP Signalling and Apoptosis: A Crossroads in Lymphocytes of Multiple Sclerosis, a Possible Role of Nutraceutics - Anna Signorile; Anna Ferretta; Maddalena Ruggieri; Damiano Paolicelli; Paolo Lattanzio; Maria Trojano; Domenico De Rasmo (MDPI AG, 2020)
Multiple sclerosis (MS) is a complex inflammatory and neurodegenerative chronic disease that involves the immune and central nervous systems (CNS). The pathogenesis involves the loss of blood-brain barrier integrity, resulting in the invasion of lymphocytes into the CNS with consequent tissue damage. The MS etiology is probably a combination of immunological, genetic, and environmental factors. It has been proposed that T lymphocytes have a main role in the onset and propagation of MS, leading to the inflammation of white matter and myelin sheath destruction. Cyclic AMP (cAMP), mitochondrial dysfunction, and oxidative stress exert a role in the alteration of T lymphocytes homeostasis and are involved in the apoptosis resistance of immune cells with the consequent development of autoimmune diseases. The defective apoptosis of autoreactive lymphocytes in patients with MS, allows these cells to perpetuate, within the CNS, a continuous cycle of inflammation. In this review, we discuss the involvement in MS of cAMP pathway, mitochondria, reactive oxygen species (ROS), apoptosis, and their interaction in the alteration of T lymphocytes homeostasis. In addition, we discuss a series of nutraceutical compounds that could influence these aspects.